The posterior temporal supraSMAS minimally invasive lifting technique using soft‐tissue fillers. (9th August 2018) - Suwanchinda, Atchima; Webb, Katherine L.; Rudolph, Christina; Hladik, Casey; Custozzo, Amanda; Muste, Justin; Schalet, Grant; Hamade, Hassan; Smith, Michael P.; Frank, Konstantin; Patel, Ashit; Cotofana, Sebastian
Abstract: Background: To investigate the effectiveness of the posterior temporal supraSMAS minimally invasive lifting technique and compared it to experiments performed in fresh human body donors by applying skin vector displacement measurement technology. Materials and methods: A total of 15 patients (14 females/1 male) with a mean age of 37.1 ± 9.4 years and a mean body mass index of 21.4 ± 3.3 kg/m 2 were included into this observational analysis. The injection procedure was additionally performed in 2 male and 1 female fresh body donors with a mean age of 85.67 ± 9.7 years and a mean body mass index of 23.83 ± 4.7 kg/m 2 . Different grades of skin laxity, variable amounts of product, and the application with and without subcision were tested and measured via three‐dimensional reconstructions and surface displacement vectors using Vectra software with VAM module. Results: Esthetic outcome was rated by an independent professional observer and by the patient immediately after the treatment (76.67% ± 17.6% vs 66.67% ± 18.1%) ( P  = 0.001) and after 1 month (80.00% ± 14.0% vs 75.00% ± 21.1%) ( P  = 0.19). Skin laxity, subcision, and the application of more than 1.0 cc per side resulted in our experimental setting in a smaller magnitude of skin displacement vectors indicating a reduced lifting effect. Conclusion: The posterior temporal supraSMAS minimally invasive lifting procedure seems to be a valid technique to treat temporal volume loss and to reduce the signs of age‐related changes in the middle and lower face, ie "marionett line" and jowl deformity.